IMPLEMENTASI KURIKULUM 2013 PADA PEMBALAJARAN PENDIDIKAN AGAMA ISLAM DALAM PENGUATAN KARAKTER RELIGIUS SISWA: Implementation Of Curriculum 2013 On Teaching Of Islamic Education In Strengthening The Religious Character Of Students - Subakri Subakri (LP2M UIN KH.Achmad Siddiq Jember, 2020)
The phenomenon of character education in Indonesia has existed along with the realization of the 2013 Curriculum. Character education was implemented even before the 2013 curriculum was implemented in schools. Character education is a school-based effort that helps a person or group of people care, understand, and act thoughtfully to apply ethical values. The purpose of character education is to help students develop optimal potential in various matters related to morality, citizenship, courtesy, ethics, behavior, being healthy, critical, and success that will meet social norms and can be accepted in society both at home and globally. . Which one day the nation's children will become human beings with quality and noble character. With character education, students can apply character values ​​such as religion, responsible, democracy, honesty, trustworthiness, leadership, fairness, and politeness in their attitude. Character education that is integrated into the 2013 Curriculum creates the next generation who is ready to face future challenges whose goal is that students have better abilities in the ability to observe, ask (interview), reason, and communicate (present) what they get or know after receiving subject matter. The 2013 curriculum, which is based on character and competence, lies in the core competencies of K-I 1, which includes spiritual attitudes; K-I 2 has social attitudes; KI-3 provides knowledge, and KI-4 skills